Properties and Structure of Functional Concrete Mixtures Modified with River Shell Powder - Sergey A. Stel’makh; Evgenii M. Shcherban’; Alexey N. Beskopylny; Nguyen Quang Hiep; Yamin Song; Diana Elshaeva; Andrei Chernil’nik; Alexandr A. Shilov; Memduh Karalar; Ceyhun Aksoylu; Yasin Onuralp Özkılıç (Salehan Institute of Higher Education, 2024)
The recycling of the aquaculture waste into clam powder reduces solid emissions and natural resources, which is important for Portland cement production. This study determines the feasibility of using recycled river shell waste as a partial replacement for cement in concrete technology. The study used normative methods and optical microscopy; the properties of cement mixtures, such as normal consistency, setting time (ST), compressive and flexural strength, were studied. Research findings have shown that the inclusion of river shell powder (RSP) in cement mixtures can reduce water demand and a decrease in setting time with increasing RSP content. It was also found that the strength of the cement mixture can be maintained with an RSP content of up to 10%. The following properties of the concrete were determined: workability, compressive strength (CS), and water absorption. Using RSP as a partial replacement for cement has been proven to elevate the slump of the fresh concrete cone. CS is maintained at a level comparable to the control composition, with an RSP content of no more than 8%, and water-absorbing is reduced by 7.31%. This study created new compositions, and the links between the ingredients, properties, and structure of cement composites modified with river shell powder were investigated. Additionally, the properties of the structure-formation process of these modified composites were studied. Doi: 10.28991/CEJ-2024-010-07-020 Full Text: PDF